2021
DOI: 10.1111/joms.12785
|View full text |Cite
|
Sign up to set email alerts
|

Grand Societal Challenges and Responsible Innovation

Abstract: Grand societal challenges (GSCs) represent complex, multi‐level, multi‐dimensional problems that require concerted efforts by various actors – public, private, and non‐profit – to be successfully addressed. Businesses – alone or in conjunction with governmental and non‐profit organizations – are relevant actors in this regard, as they represent a source of innovation. Responsible innovation (RI) is a framework that allows for the governance and evaluation of innovations with regard to their potential harmful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 122 publications
0
47
0
2
Order By: Relevance
“…Such a mandate calls for empirical and theoretical attention to how organizations influence and shape the trajectories of social systems and expands traditional ways of studying how organizations address or are affected by GC (Mair & Seelos, 2021). Illustrations for a traditional perspective are Brown et al (2022), who identified organizational survival as the key dependent variable in GC research, or Voegtlin et al (2022), who identified responsible innovation as an approach by which businesses help solve GC. A third mandate perspective expands a focus on solving GC towards imagining and assessing possibilities and roles for organizations to generate fewer 'grand' problems in the first place (Ackoff, 1981).…”
Section: Broadening Our Theoretical Scopementioning
confidence: 99%
See 2 more Smart Citations
“…Such a mandate calls for empirical and theoretical attention to how organizations influence and shape the trajectories of social systems and expands traditional ways of studying how organizations address or are affected by GC (Mair & Seelos, 2021). Illustrations for a traditional perspective are Brown et al (2022), who identified organizational survival as the key dependent variable in GC research, or Voegtlin et al (2022), who identified responsible innovation as an approach by which businesses help solve GC. A third mandate perspective expands a focus on solving GC towards imagining and assessing possibilities and roles for organizations to generate fewer 'grand' problems in the first place (Ackoff, 1981).…”
Section: Broadening Our Theoretical Scopementioning
confidence: 99%
“…(2022), who identified organizational survival as the key dependent variable in GC research, or Voegtlin et al. (2022), who identified responsible innovation as an approach by which businesses help solve GC. A third mandate perspective expands a focus on solving GC towards imagining and assessing possibilities and roles for organizations to generate fewer ‘grand’ problems in the first place (Ackoff, 1981).…”
Section: Towards Principles For Management Research On Challenges Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Framed in social responsibility, organizations have the opportunity to contribute not only to mitigating the difficult conditions of forced migration the crisis has led to, but to also enhancing their innovation and creativity through inclusive work environments. Thus, innovation makes companies globally competitive in a highly complex and uncertain business environment while promoting a better society (Voegtlin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Innovation has become more tightly connected with the grand societal challenges addressed by the UN Sustainable Development Goals (SDGs) (e.g., Coenen et al, 2015 ; Tödtling et al, 2022 ; Voegtlin et al, 2022 ). At EU level, concepts such as responsible research and innovation (RRI) (Stilgoe, Owen, and Macnaghten, 2013 ; Von Schomberg, 2013 ; Thapa et al, 2019 ) and mission-oriented research and innovation reflect this new focus on societal goals, inclusion and sustainable transitions (Mazzucato, 2018 ; Hekkert et al, 2020 ; Hill, 2022 ).…”
mentioning
confidence: 99%